THE ROLE AND IMPORTANCE OF COMPUTER GAMES IN EDUCATION (Scientific journal of the Fergana State University, 2024)
The computer game industry today has become larger than the global music and movie industries. The influence of computer games on today's youth is comparable to the cultural influence of music, political movements, and even religion on youth culture of the past. Recently, computer games have attracted a wide variety of people to use computers. They have led to the proliferation of computers in the lives of people who previously had no incentive to use them. Computer games today are gaining unprecedented access into people's homes, minds and souls. Consequently, it has become increasingly important for game developers and educators to study the use of computers to improve the education offered to the next generation of students. Computer games can be used to improve the form of education and even make computers unique learning tools. This paper will present current scenarios of using computer games for education and learning purposes. It will also look at areas where the immense potential of computer games as a learning tool can be utilized to educate a new generation of students who are accustomed to computer games. New possibilities for computer games as cognitive tools will also be projected.